Uncertainty, Financial Frictions and Nominal Rigidities : A Quantitative Investigation - Cesa-Bianchi, Ambrogio (IMF Working Papers; Working Paper ;, 2017)
Are uncertainty shocks a major source of business cycle fluctuations? This paper studies the effect of a mean preserving shock to the variance of aggregate total factor productivity (macro uncertainty) and to the dispersion of entrepreneurs' idiosyncratic productivity (micro uncertainty) in a financial accelerator DSGE model with sticky prices. It explores the different mechanisms through which uncertainty shocks are propagated and amplified. The time series properties of macro and micro uncertainty are estimated using U.S. aggregate and firm-level data, respectively. While surprise increases in micro uncertainty have a larger impact on output than macro uncertainty, these account for a small (non-trivial) share of output volatility.